2020
DOI: 10.1177/1938640020950117
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the Radiographic Measurement of the Hallux Interphalangeal Angle

Abstract: Background The hallux valgus interphalangeus (HVI) deformity has a common association with hallux valgus and hallux rigidus. The HVI is formed by the angle between the long axes of the proximal and distal phalanges. The normal value for this angular deformity in the coronal plane is less than 10°. The aim of this study was to analyze the intra- and inter-observer reliability of measuring the interphalangeal angle by orthopaedic surgeons. This study is the first study to evaluate specifically the reliability an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…In our study, intraobserver and interobserver agreement and consistency for HVA, IMA, and IPA demonstrated excellent reliability, similar to the results found by Chi et al 13 for HVA and IMA, and to the results found by Khademi et al 32 for IPA. We found good intraobserver and interobserver reliability for DMAA, different from the results presented by Vittetoe et al, 68 who obtained excellent intraobserver reliability and poor interobserver reliability, and the results presented by Lalevée et al, 34 who obtained excellent intraobserver and interobserver reliability.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, intraobserver and interobserver agreement and consistency for HVA, IMA, and IPA demonstrated excellent reliability, similar to the results found by Chi et al 13 for HVA and IMA, and to the results found by Khademi et al 32 for IPA. We found good intraobserver and interobserver reliability for DMAA, different from the results presented by Vittetoe et al, 68 who obtained excellent intraobserver reliability and poor interobserver reliability, and the results presented by Lalevée et al, 34 who obtained excellent intraobserver and interobserver reliability.…”
Section: Discussionsupporting
confidence: 91%
“…There is growing interest in the use of minimally invasive surgical techniques (MIS) for the treatment of hallux valgus (HV), with an increasing number of published studies including clinical series, radiologic validations, cadaveric studies, comparative studies, and technical reports on MIS techniques. 1,4,[8][9][10][15][16][17][18][19][20][21]23,[26][27][28][29][30][31][32][33][34][35][36][39][40][41][42][43]45,55,[59][60][61][62][63][64]66,70 Five recent systematic reviews concluded that MIS is a safe and reliable technique for hallux valgus correction. 6,11,28,44,65 Among the procedures to treat HV, the distal chevron metatarsal osteotomy was first described in 1962 and remains a widely accepted technique.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation